Microstructure-based appearance rendering for feathers. (February 2022) - Baron, Jessica; Dhillon, Daljit Singh; Smith, N. Adam; Patterson, Eric
Abstract: The appearance of a real-world feather is the result of light interactions with complex, patterned structures of varying scale; however, these have not yet been modeled for accurate rendering of feathers in computer graphics. Previously published works related to production and research have presented simplified curve models to represent the appearance of feathers. In this work we present why these approaches are not sufficient using imaging from real feathers along with motivation for a specific appearance model for feathers. We also propose and compare a new technique that takes into account the detailed substructures of feathers and their role in rendering an accurate far-field appearance. Our proposed method lends a high degree of photorealism for rendering feathers in visual-effects and content-creation applications. Graphical abstract: Highlights: Evidence and discussion motivating development of feather-specific shading models. Presentation of research questions and possible approaches. A new technique representing far-field appearance from scattering by substructures.